Analisis SWOT dalam Pengembangan Ekonomi Kreatif di Provinsi Banten: Review Potensi, Tantangan, dan Strategi Berbasis Governance - Rozikin, Rozikin; Nugroho, Kandung Sapto (FIA Unkris Press, 2025)
Creative economy has become one of the pillars of regional development in Indonesia, including in Banten Province. There is significant potential in the tourism, cultural, and MSME sectors, which are continuously being developed by local governments through medium-term development policies. However, the development of the creative economy still faces various challenges, such as limited human resources, institutions, and market access. This research reviews the development of the creative economy in Banten Province by integrating public policy study results, dependency theory, and local innovation practices based on ecotourism. Through a SWOT analysis, this article formulates development strategies that emphasize collaboration among actors (Penta Helix), increasing human resource capacity, product diversification, and strengthening local branding. The study's results show that the development of the creative economy in Banten must be directed towards sustainable, independent models that are community-oriented to avoid falling into independency patterns global economic.